An Analysis of Injury Incidence in Adult Male Soccer Players: A literature Review - Alfarraj, F.; Newman, P.; Witchalls, J.; Bousie, J. (Journal of Science and Medicine in Sport, 2021)
Background: Soccer players experience a high rate of injury, which impacts on individual and team performance, due to the physical demands and complex movements involved in the game. These combine with external variables, such as contact from other players, to increase injury potential. To reduce injury burden, preventative strategy requires an updated understanding of injury incidence, location, and severity. This literature review summarises reported epidemiology of adult male soccer injuries within the last decade. Methods: Literature was taken from a comprehensive online search of the databases CINAHL, SPORTDiscus and MEDLINE. Papers that reported data relating to the average duration of lost time due to players' injuries were included, in order to maintain the consistency of injury definitions. Both experimental and/or observational studies were included. Injury distribution of training sessions against match scenarios was analysed, with a focus on injury mechanisms, circumstances, severity, and injury location. Results: A total of 1621 records resulted from the electronic database search, and 15 research studies were included that assessed 9931 players, with an analysis of 6903 injuries. Of these 15 studies, 12 considered all body locations, one concentrated on the groin, one focused on the knee, one reported hamstring injuries. Overall, the injury incidence rate was between 1.2 and 20 injuries per 1000 hours of physical exposure to soccer; 0.51 to 10 during a training session; and 4.77 - 82.25 for match-play. The most frequent locations of injury were the lower limbs (64.2-94%), the thigh (15-37%), knee (11-22%), and ankle (10-19.3%). Moderate severity injuries (8-28 days-lost) for thigh and knee were the most common, representing up to 6.3%, 5.6% respectively of all-time loss. Conclusion: Lower limb injury rates in soccer players have remained an issue over the last ten years. Evidence collated in this review indicates that prevention and rehabilitation of lower limb injuries should be a focus in adult male soccer, with particular emphasis on thighs, knees, hip/groin and ankles. The higher incidence rates in games indicate a potential for differential injury mechanisms to be involved between matches and training. It is recommended that future studies standardise data collection by focussing on the consensus statements on injury definition and data collection procedures and analysing the specific diagnoses or clinical concepts of the injury.